2021
DOI: 10.1128/jvi.02430-20
|View full text |Cite
|
Sign up to set email alerts
|

Punctuated Loci on Chromosome IV Determine Natural Variation in Orsay Virus Susceptibility of Caenorhabditis elegans Strains Bristol N2 and Hawaiian CB4856

Abstract: Host-pathogen interactions play a major role in evolutionary selection and shape natural genetic variation. The genetically distinct Caenorhabditis elegans strains, Bristol N2 and Hawaiian CB4856, are differentially susceptible to the Orsay virus (OrV). Here we report the dissection of the genetic architecture of susceptibility to OrV infection. We compare OrV infection in the relatively resistant wild-type CB4856 strain to the more susceptible canonical N2 strain. To gain insight into the genetic architecture… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 67 publications
2
19
0
Order By: Relevance
“…Additionally, JU1580 nematodes were taken along as a highly susceptible control (FĂ©lix et al, 2011;Sterken et al, 2014). We confirmed that CB4856 was less susceptible than N2 after exposure to different concentrations or OrV and that JU1580 was more susceptible than N2 (Figure 3B) (FĂ©lix et al, 2011;Sterken et al, 2014Sterken et al, , 2021.…”
Section: The Antiviral Response In Strains With Distinct Pals-22 Pals-25 Haplotypessupporting
confidence: 57%
See 1 more Smart Citation
“…Additionally, JU1580 nematodes were taken along as a highly susceptible control (FĂ©lix et al, 2011;Sterken et al, 2014). We confirmed that CB4856 was less susceptible than N2 after exposure to different concentrations or OrV and that JU1580 was more susceptible than N2 (Figure 3B) (FĂ©lix et al, 2011;Sterken et al, 2014Sterken et al, , 2021.…”
Section: The Antiviral Response In Strains With Distinct Pals-22 Pals-25 Haplotypessupporting
confidence: 57%
“…(Figure 3B) (FĂ©lix et al, 2011;Sterken et al, 2014Sterken et al, , 2021. Moreover, we explored the difference in the N2 and CB4856 phenotype further by staining infected nematodes using Fluorescent in situ Hybridization (FISH).…”
Section: The Antiviral Response In Strains With Distinct Pals-22 Pals-25 Haplotypesmentioning
confidence: 99%
“…Blue dots indicate Tajima's D values for pals-genes. Sterken et al, 2021). Moreover, we explored the difference in the N2 and CB4856 phenotype further by staining infected nematodes using Fluorescent in situ Hybridization (FISH).…”
Section: The Antiviral Response In Strains With Distinct Pals-22 Pals-25 Haplotypesmentioning
confidence: 99%
“…The collection contains C. elegans nematodes from every continent except Antarctica and each isotype in the CeNDR collection has been sequenced ( Cook et al., 2017 ). Previous research found that genetic variations in the genes drh-1 and cul-6 change susceptibility to the OrV ( Ashe et al., 2013 ; Sterken et al., 2021 ), yet most likely additional genetic variants can influence host-virus interactions in nature. The CeNDR database provides an ideal platform to investigate worldwide genetic variation and traces of evolutionary selection in antiviral genes in C. elegans.…”
Section: Introductionmentioning
confidence: 99%
“…Recently multiparental RIL (mpRILs) populations have been developed in C. elegans ( Noble et al 2017 ; Snoek et al 2019 ). These populations have been created using other strains than the most frequently used N2 strain and the Hawaiian CB4856 strain ( Li et al 2006 ; Doroszuk et al 2009 ; Rockman and Kruglyak 2009 ; Li et al 2010 ; Vinuela et al 2010 ; Rodriguez et al 2012 ; Vinuela et al 2012 ; Snoek et al 2013 , 2014, 2014 , 2017 , 2020; Stastna et al 2015 ; Sterken et al 2015 , 2017 , 2019 , 2021 ; Thompson et al 2015 ; Kamkina et al 2016 ; Nakad et al 2016 ; Singh et al 2016 ; Jovic et al 2017 ; Jovic et al 2019 ; Evans et al 2021 ). In this study, we used the population of 200 mpRILs, derived from an advanced cross between four wild types: JU1511 and JU1941 isolated from Orsay (France) and JU1926 and JU1931 isolated from Santeuil (France) (kindly provided by MA FĂ©lix, Paris, France; Volkers et al 2013 ; Snoek et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%